The Green Economy for Sustainable Growth: Opportunities in Indonesia’s Economic Transformation - Bulgis Khumairoh; Darmanto Darmanto; Asrianti Dja’wa; Halek Mu’min (Green Publisher, 2025)
This study opens by noting that the global growth model is shifting toward a green economy that reconciles prosperity with ecological limits. The objective is to identify Indonesia’s green-economy opportunities. Using a qualitative, library-based design, we synthesize peer-reviewed studies, official statistics, and policy documents. Findings reveal six opportunity channels. (1) Investment momentum: rising renewable-energy finance and project digitalization are attracting domestic and foreign capital, signaling policy credibility. (2) Structural and sectoral diversification: clean-tech and circular practices are spilling over into components, services, and agro-processing, deepening value chains. (3) Labor-market transformation: green industries create safer, higher-quality jobs, provided reskilling systems align training with firm needs. (4) Macroeconomic resilience: greater renewable penetration reduces import dependence and exposure to price shocks while supporting external balance. (5) Trade competitiveness and innovation: certification, traceability, and eco-innovation differentiate exports and open access to sustainability-sensitive markets. (6) Regional development opportunities: microgrids, green industrial parks, and subnational finance can diffuse benefits to lagging provinces. The study implies that Indonesia can convert the green transition into a long-term engine of inclusive growth by scaling de-risked green finance, accelerating grid modernization, and embedding portable green skills across education and workforce programs while advancing place-based industrial strategies and data-driven supply-chain governance at national scale.